Understanding preeclampsia: angiogenesis biomarkers in focus - Kyrychenko, M. M.; Siusiuka, V. G.; Deinichenko, O. V.; Кириченко, Михайло Михайлович; Сюсюка, Володимир Григорович; Дейніченко, Олена Валеріївна (Chicago : European Scientific Platform, 2024)
This article delves into preeclampsia, a significant pregnancy complication marked by high maternal mortality. It highlights the central role of angiogenesis biomarkers, particularly PlGF and sFlt-1, in understanding the disease's pathogenesis and aiding early diagnosis. The study examines the predictive value of the sFlt-1/PlGF ratio for risk stratification, emphasizing the potential for timely intervention to improve maternal and fetal outcomes. Further research is encouraged to enhance clinical applications and explore preeclampsia's underlying mechanisms.